THE LOCAL IN VIDEOGAMES: TEXTUALITY, MEANING-MAKING, AND AFFORDANCE - Thabet, Tamer; Christiano, Ana Priscilla; Vilas Boas da Silva, Alexandre (Revista Alere, 2017)
This article aims at relating a research project about locality of videogame content to the larger body of knowledge in game studies. Based on the belief that video games function as a cultural voice that is not generation-specific, in the same way films are, the research project "Local Videogames" seeks to create and apply a special model of building game narratives out of local experiences; stories from the collective popular memory of one region as opposed to the familiar and metropolitan narratives. The goal of our article is to place the project and its game production in the perspective of game studies. We attempt to construct this relation in the light of Melcer’s (2015) study and based on key concepts in game studies: gamification, textuality, flow, meaning-making, and affordance.